Microencapsulação por gelificação iônica e interação eletrostática do corante de buriti (Mauritia flexuosa L. f.) - Aranha, Caroline Pereira Moura [UNESP] (2015)
The aim of this work was to study the microencapsulation process by ionic gelation associated with the electrostatic interaction of the dye extracted from the buriti pulp. Initially the surface tension, density and rheological properties of the solutions of alginate and pectin, and buriti oil emulsions, were determined. For the ionic gelation step, two alternative biopolymers were tested: alginate and amidated low-methoxyl pectin, both being gelled in the presence of calcium ions. As core material was used buriti oil, which was extracted from the palm fruits by the Bligh-Dyer method. The produced microcapsules were coated by electrostatic interaction with whey protein concentrate (WPC). The proteins conditions for the adsorption of on the surface of alginate or pectin particles were determined by the Zeta potential analysis of the dispersions of protein and polysaccharides. This analysis also gave the isoelectric point of the whey proteins. The atomization process for ionic gelation was carried out at different conditions of air and feed flow rate. The influence of these parameters on the characteristics of buriti oil microparticles produced with alginate:WPC and pectin:WPC was evaluated by determining: the dimensionless numbers (Reynolds, Weber and Ohnesorge); the average particle diameter obtained by ionic gelation only and after interaction with WPC; the encapsulation efficiency and carotenoid retention; and color parameters (a*, b*, L*, C and h). From these results, four best conditions of the atomization process to each pair of polymers studied were selected. The particles produced using the selected conditions were evaluated regarding the mean diameter after lyophilization, the FTIR-ATR and morphology using microscopy: optical, scanning electron and confocal laser. The capsules showed high encapsulation efficiency and carotenoids retention, however showed no difference in their coloring ...